NIH Career Development Awards in Clinical and Translational Science Award Institutions: Distinguishing Characteristics of Top Performing Sites - Guerrero, Lourdes R. (Clin Transl Sci, 2014)
PURPOSE: To identify and disseminate the organizational characteristics of “top performing” National Institute of Health (NIH) Clinical and Translational Science Awards (CTSA) institutions in regards to career development, using the number of new K awards received per year to rank institutions and comparing these with non‐CTSA institutions. METHODS: The authors analyzed the organizational characteristics of all 61 CTSA institutions from 2006 to 2013 using the American Association of Medical Colleges Organizational Characteristics Database and K Award funding details using NIH RePORT. RESULTS: Five of the “top 10 performing” institutions are in the western region, and six out of the ten are public schools. Three of the “top 10 performing” institutions receive most of their K awards through two funding mechanisms—the K08 (mentored clinical scientist research award) and K23 (mentored patient‐oriented research career development awards). Notably, these three institutions lack a KL2 program. CONCLUSION: The CTSA network of institutions is committed to developing the next generation of physician scientists in order to meet the pressing health needs of society. Educators and evaluators within this network may need to provide training to junior investigators beyond the traditional KL2 programs in order to advance their career development as physician scientists and clinical translational researchers.